Macroeconomic Determinants of LQ 45 Stock Returns in Indonesia: An ARDL Analysis - Anisa Maulita Suryana; Faizul Mubarok; Ahmad Rodoni; Aini Masruroh (Agregat: Jurnal Ekonomi dan Bisnis, 2026)
The LQ45 index is widely recognized as a key indicator of the Indonesian capital market, representing the performance of large-cap and highly liquid listed firms, while remaining sensitive to prevailing macroeconomic conditions. This study analyzes the influence of inflation, the policy interest rate, the USD/IDR exchange rate, and overall market performance measured by IHSG returns on LQ45 stock returns over both short-run and long-run horizons. Monthly data spanning January 2009 to August 2025 are utilized, drawn from the Indonesia Stock Exchange, Bank Indonesia, and official statistical sources. The empirical analysis employs an Autoregressive Distributed Lag (ARDL) approach, which is appropriate for examining relationships among variables with different orders of integration. The Bounds Test results provide evidence of a long-term equilibrium relationship between LQ45 returns and the selected macroeconomic variables. Long-run estimates indicate that inflation and IHSG returns have a positive and statistically significant effect on LQ45 returns, whereas the policy interest rate and exchange rate do not exhibit significant influences. In the short run, exchange rate fluctuations exert a significant negative impact on LQ45 returns, while the policy interest rate remains statistically insignificant. Diagnostic tests confirm the structural stability of the model based on the CUSUM and CUSUMSQ criteria, and heteroskedasticity concerns are addressed through the use of robust standard errors. This study extends existing literature by incorporating IHSG returns as a market-wide control variable and employing a long monthly dataset covering multiple monetary policy regimes. These findings imply that monetary authorities and capital market regulators should pay close attention to inflation dynamics and aggregate market conditions (IHSG) when formulating financial stability policies. Meanwhile, investors may consider these indicators as key determinants in their investment decisions regarding LQ45 constituents